Empowering Indonesian Migrant Workers Through Sharia Financial Literacy and Household Management - Amir Mukadar; Surya Adi (Future Tecno-Science Publisher, 2025)
Indonesian migrant workers (Pekerja Migran Indonesia/PMI) are economically significant contributors to household welfare and national remittance flows, yet many remain exposed to weak financial planning, informal borrowing, and limited access to appropriate financial services. This community service program, implemented in Kuala Lumpur and Selangor, Malaysia, in collaboration with the Overseas Branch of Muhammadiyah Malaysia (PCIM Malaysia), aimed to strengthen Sharia-based financial literacy and practical household financial management among PMI communities. The program involved 87 Indonesian migrant workers through structured workshops, budgeting exercises, product-orientation sessions, and peer mentoring. Evaluation was conducted using pre- and post-program knowledge tests, follow-up budgeting checklists, attendance records, and focus group discussions. The mean financial literacy score increased from 51.3 to 76.8 out of 100, while the proportion of participants maintaining a written household budget increased from 23% at baseline to 71% at the eight-week follow-up. Participants also reported stronger awareness of riba, zakat, infaq, halal savings instruments, and Sharia-compliant alternatives to informal borrowing. These findings indicate that culturally grounded, faith-sensitive, and practice-oriented financial education can improve both knowledge and applied financial behaviour among migrant worker communities. The program offers a replicable model for diaspora-based community empowerment through mosque, community, and Muhammadiyah networks.